Effect of Titanium Dioxide on Adhesion and Conductivity Behavior of Polyaniline/Alkyd Composite for Solar Cell Application. Issue 1 (19th December 2018) - Phang, Sook Wai; Ramli, Mariam Fadzlina; Khong, Choy Hung; Lim, Wen Huei; Gan, Seng Neon
Abstract : This study attempts to improve the adhesion and conductivity of polyaniline (PAni) by incorporating an alkyd and titanium dioxide (TiO2 ), respectively. PAni with different TiO2 content (10, 20, and 40%) are synthesized through chemical oxidation method by using aniline (Ani) monomer, dioctyl sodium sulfosuccinate (AOT) dopant, and ammonium persulphate (APS) oxidant at 0 °C for 24 h. In order to improve the adhesion of PAni‐TiO2 on fluoride doped‐tin oxide (FTO) glass prior to its application as counter electrode (CE) in Dye‐Sensitized Solar Cell (DSSC), a palm oil‐based alkyd is added into PAni‐TiO2 composite. Chemical structures of PAni‐TiO2 /Alkyd are confirmed by Fourier transform infrared spectrophotometer (FTIR) and ultraviolet‐visible (UV‐Vis) spectrophotometry analyses. Conductivity measurement is determined by using four point probe method and adhesion test is performed following ASTM D3599. Results showed that conductivity of PAni had significantly improved from 3.53 × 10 −3 (without TiO2 ) to 8.16 × 10 −3 –6.59 × 10 −2  S cm −1 (with TiO2 ). However, the conductivity of all PAni‐TiO2 /Alkyd samples on FTO glass showed high conductivity (6.11–6.32 × 10 2  S cm −1 ) and better adhesion behavior on FTO glass except for the sample with 40% of TiO2 . The plausible mechanisms between PAni‐TiO2 /Alkyd and FTO glass are proposed in this study based on the FTIR and UV‐Vis analyses.